Pseudascarophis brasiliensis sp. nov. (Nematoda: Cystidicolidae) - Pereira, Felipe Bisaggio (2013)
A new species of Pseudascarophis Nematoda: Cystidicolidae) found in the stomach of Kyphosus sectatrix (Linnaeus) (Kyphosidae), off Rio de Janeiro, Brazil, is described. The new species can be differentiated from the other congeners by the presence of lateral alae, distinct but inconspicuous cephalic papillae at the anterior end, three pairs of precloacal and one pair of adcloacal papillae in males, egg morphology and morphometry of glandular oesophagus and spicules. Pseudascarophis tropica is transferred to Ascarophis as Ascarophis tropica (Solov?eva) comb. n. due to its ambiguous diagnosis.